Mengelola SDM dalam Organisasi Karang Taruna yang Berkualitas - Retnowati, Ayu Nike; Sitorus, Veronica Rohali (LPPM UNIBI, 2023)
Karang Taruna Manjahlega is a social organization that is a forum for the development of community members based on a sense of social responsibility based on the principle of from, by and for the community. Mobilizing youth for social welfare for the community that can contribute to the scope of the village or sub-district. The role and vision of Karang Taruna in society have the meaning of making Karang Taruna an important organization to be able to facilitate positive youth activities. The voluntary principle applied makes it difficult for Karang Taruna to develop because the involvement and other roles in the lives of its members make many activities not run optimally. Community Service Activities with the theme of Managing Quality Human Resources in Karang Taruna, aim to increase awareness of Karang Taruna Manjahlega members regarding the sense of belonging and responsibility for the organization so that they can become a more creative and innovative Karang Taruna, fostering the enthusiasm of Karang Taruna members in carrying out activities that help in community welfare. The method used in PKM activities is counseling by involving interactive activities with participants to increase familiarity between Karang Taruna members in improving the quality and performance of the organization in a sustainable manner.